Efficacy of scalp cooling in reducing alopecia in early breast cancer patients receiving contemporary chemotherapy regimens. (October 2018) - Chan, Arlene; Bauwens, Astrid; Pontre, Sally; Jackson, Sally; McGlone, Frances; Ernenwein, Tracie; Chih, Jun; Reid, Christopher
Abstract: Introduction: Hair loss as a result of chemotherapy for early breast cancer (EBC) is a frequent and distressing side effect. Minimising hair loss may improve mood and body image. Our aim was to determine scalp cooling (SC) efficacy in EBC patients receiving contemporary chemotherapy regimen, to inform future patients choice to use SC or not. Methods and Results: Prospective cohort study of 60 stage 1–3 EBC patients recommended to receive taxane or anthracycline-taxane chemotherapy regimens. The primary outcome was incidence of minimal hair-loss (MHL - defined as 60% Dean grade 1 or 2). Patients were categorised by chemotherapy (3 groups) and randomised 1:1 within each group to two scalp cooling temperature settings using the Dignitana Dignicap machine (secondary endpoint). Patients reported degree of hair loss using the Dean score on day 1 of each cycle and following the last chemotherapy. Results: On an intention-to-treat basis, 33% of patients reported MHL, thus our primary endpoint was not achieved. Patients receiving taxane-only chemotherapy had the highest rate of MHL (45%). No other factors (including hair type, age, body weight, temperature setting) predicted for MHL. Patient-reported anxiety reduced significantly in all patients, but no difference was observed for depression or body image irrespective of degree of hair loss. SC-related adverse events were uniformly of low grade and all resolved. We would recommend the use of SC for all patients receiving taxane-based chemotherapy, with its use for those patients recommended for anthracycline-taxane regimens being made on an individual basis. Trial Registration anztr.org.au ACTRN12615001106527 . Highlights: Minimising chemotherapy-induced alopecia was unimportant in 30% EBC patients. Less than 50% alopecia achieved in 45% patients on docetaxel and cyclophosphamide. Less than 50% alopecia achieved in 20–35% patients on anthracyclines. Degree of alopecia did not influence depression, anxiety or body image.